2014
DOI: 10.1080/14786419.2014.971793
|View full text |Cite
|
Sign up to set email alerts
|

Compositions of the seed oil of theBorago officinalisfrom Iran

Abstract: In order to investigate the composition of borage (Borago officinalis L.) seed oil, this research was performed under the field conditions at Shahriyar and Garmsar zones, Iran during the 2012 planting year. The oil yield of borage was 31.46% and 33.7% at Shahriyar and Garmsar zone, respectively, and nine and eight fatty acids were identified in the seed oil of borage at Shahriyar and Garmsar, respectively - palmitic, linoleic, stearic and γ-linolenic acids were dominant in the seed oil of borage from both zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Borage leaves are an inexpensive crude material for the production of polyphenols, and disposal of these leaves needs a high cost, which can be limited by its utilization (Krishnaiah et al, 2011). Many unsaturated fatty acids, for example, palmitic, stearic, linoleic and α-linolenic acids are found in flowers of borage (Morteza et al, 2014 andRamandi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Borage leaves are an inexpensive crude material for the production of polyphenols, and disposal of these leaves needs a high cost, which can be limited by its utilization (Krishnaiah et al, 2011). Many unsaturated fatty acids, for example, palmitic, stearic, linoleic and α-linolenic acids are found in flowers of borage (Morteza et al, 2014 andRamandi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Borago officinalis seed oil is used in pharmaceutical products, especially for its high content in α-linolenic acid, an essential and unusual fatty acid (10,43). It has been shown that palmitic, linoleic and stearic acids were dominant in the seed oil of borage (44). Wettasinghe and Shahidi investigated the antioxidant and reactive oxygen species (ROS) scavenging properties of borage meal extract (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its potential market for gamma linolenic acid (GLA), it has been the subject of increasing agricultural interest and different fatty acids obtained from the seeds [130]. In addition to GLA, borage seeds contain stearic, erucic, linoleic, palmitic, oleic, α-linolenic, and erucic acids [131][132][133][134]. GLA is an omega-6 essential fatty acid that has been considered as having many positive therapeutic impacts, such as the treatment of diabetes, arthritis, heart disease, atopic eczema, cyclic mastalgia, and multiple sclerosis [135,136].…”
Section: Key Points Referencesmentioning
confidence: 99%
“…[123][124][125][126] The main reasons for membrane disruption are increased free fatty acid levels and free radical productivity by lipid per oxidation. [126][127][128][129][130] The seeds also contain palmitic, linoleic, stearic, α-linolenic, oleic, erucic, and erucic acids [130][131][132][133][134][135] Gamma-linolenic acid showed the potential to relieve the symptoms and signs of various chronic inflammatory diseases, such as atopic dermatitis and rheumatoid arthritis. [135][136][137][138][139][140] Gamma-linolenic acid can also be appropriate in respiratory, gastrointestinal, and cardiovascular disorders.…”
Section: Key Points Referencesmentioning
confidence: 99%